Exploration of microRNAs and their targets engaging in the resistance interaction between wheat and stripe rust - Feng, Hao; Zhang, Qiong; Wang, Bing; Fu, Yanping; Huang, Lili; Wang, Xiaojie; Kang, Zhensheng (Frontiers in Plant Science, 2015)
Wheat stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is one of the most destructive diseases of wheat worldwide. miRNAs are important regulators, they play very central roles in plant organ development, vegetable phase change and defense responses. In this study, two miRNA libraries from wheat cultivar Xingzi 9104 (XZ) challenged with the avirulent Pst race CYR32 and sterile water were constructed, respectively. A total of 596 miRNA candidates were obtained. 420 wheat-specific candidate miRNAs were screened in adult plants challenged with Pst using microarray-based analyses. We analyzed the abundance of candidate miRNAs, and the levels of a subset of candidate miRNAs were determined by quantitative real time PCR (qRT-PCR). The qRT-PCR results indicated that some miRNAs were involved in the incompatible interaction between wheat and Pst. In addition, we identified some miRNAs differentially expressed in different leaves. Additionally, the target genes of wheat miRNAs were confirmed by using degradome sequencing technology. Most of the annotated target genes are related to signal transduction, energy metabolism, and other functions. We selected some target genes for relative expression analysis using qRT-PCR, and found that RabGAP/TBC domain-containing protein, zinc finger protein and Cysteine-rich receptor-like protein kinase 41 may play important role in the incompatible interaction between XZ and CYR32. Intriguingly, miRNAs and target gene seem to form a complicated regulation network that regulates the wheat-Pst interaction. Our data provide the foundation for evaluating the important regulatory roles of miRNAs in the wheat-Pst interaction.